PEMAKNAAN RASISME DALAM POLA PIKIR MASYARAKAT KOTA BATAM - Gladies Imanda Utami Rangkuty; Muhammad Ikhsan Kasturi; Shanice Lu; Vincent Vincent; Salsabila Pane; Angeline Goh; Yanty Yanty; Jihan Karisma; Muhammad Sulthon Fahmi; Evan Farell; Henny Henny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Racism can be interpreted as the practice of labeling and evaluating individuals to other individuals by races or striking differences. Racism is one of the many problems faced by the Indonesians, especially Papuans. The issue of racism that had shocked Indonesia recently involved Papuan students in Surabaya, consequently made Papuans feel furious about the action. Therefore, we want to remind the public, especially the people of Batam, to always respect differences from each other with some actions. The method we use in carrying out actions to motivate the community is the quantitative method and collecting the data by distributing a number of questions to respondents to fill out. We distributed online questionnaires to 30 separate respondents through Google form. In addition, the result of this action is that we produced a tote bag and shared it with the community as a solution to raise awareness of racism in Batam. In addition, we also made a short animated video with attractive animation and will be published through Instagram. With the distribution of these tote bags and short animated videos, many people in Batam should start to think about their position and a new perspective on racism.